2013
DOI: 10.5155/eurjchem.4.1.53-57.733
|View full text |Cite
|
Sign up to set email alerts
|

An efficient route for the synthesis of some monoazo disperse dyes derived from nicotinic acid derivatives

Abstract: KEYWORDSEthyl 2-amino-3-cyano-4-phenylnicotinates (8), could be readily synthesized via reacting ethyl propiolate with benzylidenemalononitrile in the presence of L-proline as a catalyst and subsequent rearrangement of the so formed 2-aminopyran (7), with acetic acid in the presence of ammonium acetate. A series of 2-amino and 2-hydroxyarylazonicotinates monoazo disperse dyes (12a-c), were prepared in a good yields via condensation of arylhydrazonals (11a-c), with active methylene nitriles. The compound 9 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Recently we have reported the synthesis of 2-amino-and 2-hydroxy-6-substituted-5-arylazonicotinates dyes [13]. Herein, in an attempt to improve and facilitate the synthesis of these disperse dyes, we report a new strategy for the preparation of these disperse dyes in better yields by condensing of arylhydrazonals 2a-c with ethyl cyanoacetate under microwave irradiation as an energy source.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently we have reported the synthesis of 2-amino-and 2-hydroxy-6-substituted-5-arylazonicotinates dyes [13]. Herein, in an attempt to improve and facilitate the synthesis of these disperse dyes, we report a new strategy for the preparation of these disperse dyes in better yields by condensing of arylhydrazonals 2a-c with ethyl cyanoacetate under microwave irradiation as an energy source.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that microwave irradiation is a beneficial method to promote diverse organic transformations that occur in remarkably reduced reaction times and improved yields [1]. As an extension of our previous studies [13] on the synthesis of a variety of 2-amino and 2-hydroxy-6-substituted-5-arylazonicotinates disperse dyes under traditional heating way. In this article, we report a new synthesis of theses dyes under microwave irradiation and their application for dyeing polyester fabrics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Al-Mousawi et al has found that in presence excess amount of ammonium acetate the amino derivative 9 is formed. In case of presence excess amount of ammonium acetate pyran-imine, 5, is attacked by NH3 ion yielding acyclic amidine 8 that then cyclizes followed by water elimination to yield compound 9 [11][12][13]. Previously, it was noted in the literature that in some cases pyridazinones 10 are the reaction products ( Figure 2-4) [14][15][16][17][18][19].…”
Section: Synthetic Approaches To Arylazonicotinate Pyrido[32c] Cinmentioning
confidence: 99%
“…These substances are believed to be formed via a 6π-electrocyclization reaction of the initially formed arylazo nicotinate 7, that generates the tricyclic intermediate product 11, which then aromatizes to produce the cinnoline derivatives, 12 (Scheme 2) [9,11,12]. (%) 3a C6H5 C6H4NO2-p CO2Et 199-201 74 3b Thien-2-yl C6H4NO2-p CO2Et 170-172 67 3c Fur-2-yl C6H4NO2-p CO2Et 242-244 75 7a C6H5 C6H4CH3-p CO2Et 180-182 84 7b C6H5 C6H4CH3-p CONH2 276-277 85 7c C6H4NO2-p C6H5 CN 276-278 85 7d C6H4CH3-p C6H5 CSNH2 166-168 72 7e CH3 C6H5 CONH2 300 74 The formed aminonictinates 9a could be readily converted to ethyl 5-p-tolyldiazenyl)-2-(aminomethyleneamino)-6-phenyl nicotinate 13 via condensation with N,N-dimethylformamide dimethylacetal (DMFDMA) in presence of ammonium acetate.…”
Section: Synthetic Approaches To Arylazonicotinate Pyrido[32c] Cinmentioning
confidence: 99%